Genomics detects population structure within and between ocean basins in a circumpolar seabird: The white‐chinned petrel - Rexer-Huber, Kalinka (2019)
The Southern Ocean represents a continuous stretch of circumpolar marine habitat, but the potential physical and ecological drivers of evolutionary genetic differentiation across this vast ecosystem remain unclear. We tested for genetic structure across the full circumpolar range of the white-chinned petrel (Procellaria aequinoctialis) to unravel the potential drivers of population differentiation and test alternative population differentiation hypotheses. Following range-wide comprehensive sampling, we applied genomic (genotyping-by-sequencing or GBS; 60,709 loci) and standard mitochondrial-marker approaches (cytochrome b and first domain of control region) to quantify genetic diversity within and among island populations, test for isolation by distance, and quantify the number of genetic clusters using neutral and outlier (non-neutral) loci. Our results supported the multi-region hypothesis, with a range of analyses showing clear three-region genetic population structure, split by ocean basin, within two evolutionary units. The most significant differentiation between these regions confirmed previous work distinguishing New Zealand and nominate subspecies. Although there was little evidence of structure within the island groups of the Indian or Atlantic oceans, a small set of highly-discriminatory outlier loci could assign petrels to ocean basin and potentially to island group, though the latter needs further verification. Genomic data hold the key to revealing substantial regional genetic structure within wide-ranging circumpolar species previously assumed to be panmictic.